P112 An Investigation of Parent and Child Perceptions of Food Allergy Practices, Protocols, and Policies in Schools - Girsch, Virginia; Foster, Jaime; Vollmer, Rachel L. (Journal of nutrition education and behavior, 2020)
Many schools implement well-meaning policies to protect children with food allergies; however, these policies oftentimes do not ease parents’ worry and concern, or leave children feeling isolated. Explore children's and parents’ perceptions of how supportive and safe their school is about food allergies. Children ages 8 to 18 with a food allergy and their parents (n = 18 pairs) across the U.S. who met the inclusion criteria completed one-on-one semi-structured phone interviews. Interviews were audio-recorded and transcribed. Content analysis was applied to the transcriptions by 2 investigators, independently, to identify themes among parents and children. Investigators met to discuss themes and reach consensus. Overall, both parents and children felt generally safe with their school's policies with some exceptions, although parents seemed to be more concerned vs their children, especially younger children. Exceptions included cross-contamination, outside food, especially home-baked items, being brought into classrooms, and the knowledge and awareness of their child's food allergies among others within the school community. Striking a balance between safety and inclusion was important to parents in normalizing life for their children. For example, a policy of a nut-table in which children who bring a lunch containing nut products may be more inclusive vs a nut-free table (where only those with food allergies sit). This would allow more freedom for those with food allergies to choose where they sit, and may make them feel more included. While schools across the U.S. have a variety of policies in place to protect children with food allergies, the social and emotional effects of these policies, in conjunction with safety, are important considerations. Policies that may need to be considered include increased food allergy training and education for teachers and staff, nut-free campuses, and banning outside food without a food label.